2011
DOI: 10.1128/mcb.01448-10
|View full text |Cite
|
Sign up to set email alerts
|

The ARID Family Transcription Factor Bright Is Required for both Hematopoietic Stem Cell and B Lineage Development

Abstract: Bright/Arid3a has been characterized both as an activator of immunoglobulin heavy-chain transcription and as a proto-oncogene. Although Bright expression is highly B lineage stage restricted in adult mice, its expression in the earliest identifiable hematopoietic stem cell (HSC) population suggests that Bright might have additional functions. We showed that >99% of Bright ؊/؊ embryos die at midgestation from failed hematopoiesis. Bright ؊/؊ embryonic day 12.5 (E12.5) fetal livers showed an increase in the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 60 publications
(104 reference statements)
6
106
0
Order By: Relevance
“…Arid3a, the founding member of the ARID family of TFs, has been characterized as a transactivator of both B lymphocyte development and cell cycle progression (Herrscher et al 1995). Loss-of-function studies revealed that >98% of Arid3a À/À mice die prior to embryonic day 11.5 (E11.5) (Webb et al 2011), suggesting a potential role in embryonic development. A recent follow-up study showed that singular loss of Arid3a is sufficient for reprogramming as well as enhancement of standard four-factor reprogramming of mouse embryonic fibroblasts (MEFs) to fully induced pluripotent stem cells (Takahashi and Yamanaka 2006;Popowski et al 2014).…”
Section: Cdx2mentioning
confidence: 99%
“…Arid3a, the founding member of the ARID family of TFs, has been characterized as a transactivator of both B lymphocyte development and cell cycle progression (Herrscher et al 1995). Loss-of-function studies revealed that >98% of Arid3a À/À mice die prior to embryonic day 11.5 (E11.5) (Webb et al 2011), suggesting a potential role in embryonic development. A recent follow-up study showed that singular loss of Arid3a is sufficient for reprogramming as well as enhancement of standard four-factor reprogramming of mouse embryonic fibroblasts (MEFs) to fully induced pluripotent stem cells (Takahashi and Yamanaka 2006;Popowski et al 2014).…”
Section: Cdx2mentioning
confidence: 99%
“…We picked Arid3a as a candidate because of its known role in FL HSCs, which are exposed to higher levels of IFN-a ( Figure 1F). 40 Examination of Arid3a protein levels in E11.5 embryonic tissues indicated that, in addition to the FL, Arid3a is expressed at sites of embryonic hematopoiesis, including the AGM, yolk sac, and placenta ( Figure 5B). 40 To determine whether Arid3a is expressed in endothelial or hematopoietic cells, we stained the AGM with CD45 and VEcadherin, and sorted by flow cytometry into the four fractions (supplemental Figure 3A- Figure 5C).…”
Section: 3839mentioning
confidence: 99%
“…40 They also have FL HSC defects, 40 but whether they are impaired in AGM hematopoiesis is unknown. We first determined whether hematopoietic progenitors are present in the Arid3a KO AGM by immunostaining for Runx1 (supplemental Figure 3F-G).…”
Section: 3839mentioning
confidence: 99%
“…3A). ARID3B is a DNA-binding protein belonging to the AT-rich interactive domain (ARID) family of transcriptions factors that are involved in diverse biologic processes (30), and HMGA2 is a member of the highmobility group AT-hook protein family and has been reported to be a Let7 target (8) and directly binds to Sox2 promoter in glioblastoma cells to induce Sox2 expression (26). To validate the bioinformatics data, we established a panel of patient samplederived CD44 À ALDH1 À OSCC cells with different combination of overexpressed Lin28B, Let7, and Spg-Let7.…”
Section: Arid3b and Hmga2 Are Targets Of Lin28b/let7 Signaling To Regmentioning
confidence: 99%